'Exploring the local: vernacularizing economic and social rights for peacebuilding within the Protestant/Unionist borderland community in Northern Ireland'. Issue 8 (14th September 2019) - Cahill-Ripley, Amanda
ABSTRACT: This paper explores the knowledge, understanding and opinions of the Protestant/Unionist borderland communities in Northern Ireland towards economic and social rights (ESR). The article seeks to establish whether economic and social rights have transformative potential for protecting and promoting their rights in the first instance and for building and sustaining peace within their communities. Based upon new primary data gathered from a small-scale empirical study, the article explores local grassroots experiences of ESR. It also examines the particularities of the post-conflict legacy in the borderlands and its impact upon attitudes to human rights and the peace process. The central contention is that despite the historical and political problematic perceptions of human rights for many in the Protestant/Unionist population of the borderlands, evidence shows there are opportunities to engage such communities with ESR in a meaningful and positive way. By vernacularizing economic and social rights, they can be made meaningful and useful to these communities, both for protecting and promoting their ESR and as a tool for peacebuilding within Northern Ireland.